Conspiracy/theory - Masco, Joseph 1964-; Wedeen, Lisa (Durham London Duke University Press, 2024)
In an era of intensified information warfare, ranging from global disinformation campaigns to individual attention hacks, what are the compelling terms for political judgment? How are we to build the knowledge needed to recognize and address important forms of harm when critical information is either not to be trusted or kept hidden? Rather than approach conspiratorial narrative as an irrational response to an obviously decipherable reality, Conspiracy/Theory identifies important affinities between conspiracy theory and critical theory. It recognizes the motivation people have—in their capacities as experts, theorists, and ordinary citizens—to search for patterns in events, to uncover what is covert and attend to dimensions of life that might be hiding in plain sight. If it seems strange that so many find themselves living in incommensurable, disorienting realities, the multidisciplinary contributors to Conspiracy/Theory explore how and why that came to be. Across history and geography, contributors inquire into the affects and imaginaries of political mobilization, tracking counterrevolutionary projects while acknowledging collective futures that demand conspiratorial engagement.Contributors. Nadia Abu El-Haj, Hussein Ali Agrama, Kathleen Belew, Elizabeth Anne Davis, Joseph Dumit, Faith Hillis, Lochlann Jain, Demetra Kasimis, Susan Lepselter, Darryl Li, Louisa Lombard, Joseph Masco, Robert Meister, Timothy Melley, Rosalind C. Morris, George Shulman, Lisa Wedeen
"Conspiracy/Theory, edited by Joseph Masco and Lisa Wedeen, examines the proliferation of conspiracy theories across the globe, demonstrating across historical periods and state projects the vital place of speculation in making and evaluating collective conditions. The essays explore the genealogical and theoretical overlaps between "conspiracy" and "critical theory," moving beyond a US focus to think in multi-sited and implicitly comparative ways about the conspiracy theories in circulation today. The volume's four sections address central theoretical issues such as knowledge production, community formation, political violence, social control, democracy, and the meaning of engaging in theoretically informed scholarship"--
CONTRIBUTORS
In English
Keywords: Conspiracy Theories; Conspiracy; Critical Theory; Truthfulness and falsehood; SOCIAL SCIENCE / Conspiracy Theories; SOCIAL SCIENCE / Anthropology / Cultural & Social; SOCIAL SCIENCE / Anthropology / Cultural & Social; Aufsatzsammlung